Rancang Bangun Aplikasi Penilaian Kinerja Guru Berbasis Website Dengan Menggunakan Metode Topsis (Studi Kasus: SDN Ketabang I Surabaya) - Putra, Kevin Rubama; A, Slamet; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
In developing competent teachers, a transparent performance appraisal program is needed for the professional and career development of teachers that can improve the quality of their performance on an ongoing basis. The current condition in the process of evaluating teacher performance at Ketabang I Surabaya Elementary School from the results of interviews with the teacher as a resource is that the assessment process does not have fixed parameters and criteria so the performance appraisal process varies each year. Currently the teacher cannot see in realtime the performance appraisal process that is running and the teacher cannot know the ranking of teacher performance results for the current period or the previous period. Based on the above problems, a solution that can help the performance appraisal process is to build a website-based teacher performance appraisal application according to the parameters or criteria using an assessment process based on the Directorate General of National Education Ministry of Education and Culture Teacher Performance Assessment (PKG) In knowing the ranking of teacher assessment results, the TOPSIS (Technique for Order Preference by Similarity o Ideal Solution) method is used, which is one of the Decision Making System (DSS) methods. With this Website-Based Teacher Performance Appraisal Application Using the Topsis Method, teachers can see the ranking directly on the dashboard for each assessment period carried out to maximize performance in the teaching and learning process.